Barrier property determination and lifetime prediction by electrochemical impedance spectroscopy of a high performance organic coating (2014)
The anticorrosion performance of an Epoxy-Mastic organic coating was evaluated during continuous immersion in saline solution using electrochemical impedance spectroscopy (EIS). The typical parameters of pore resistance and charge transfer resistance were determined employing an equivalent electric circuit. Constant phase elements (CPE) were used in order to determine fraction of water absorbed, mass diffusion, solubility and the swelling coefficients, as well as to predict the failure times of the coating. The results found by EIS measurements match very well with the high resistance to deterioration exhibited by the coating. It was also found that the excellent protection performance of the coating was mainly due to low water solubility and low permeability.